Direitos de propriedade e usos econômicos da terra:um estudo de caso de assentamentos de reforma agrária no sul do Pará - Guedes, Sebastião Neto Ribeiro [UNESP]; Reydon, Baastian Philip; Florêncio, Celso Aparecido (My University, 2011)
This article discusses the Brazilian land problem related to property rights of rural land. After emphasizing the importance of land policies in order to define and distribute rural land properties rights, we show how in Brazil the institutions of rural land registering and cadastering as separated processes debilitates the property rights, making them vulnerable to the effective occupying actions. In order to illustrate it, in this article we analyze Data based in a Case Study of conflict and property rights distributions in an important farming and mining region of southern Para state, in Brazil.

O artigo discute o problema fundiário brasileiro relacionado aos direitos de propriedade da terra rural. Ao demarcar a importância das políticas agrárias para definir e distribuir direitos de propriedade, o artigo analisa como, no Brasil, tais direitos foram estruturados de maneira bastante peculiar, permitindo o divórcio entre registro e cadastro de terras. Uma das consequências disso foi fragilizar os direitos de propriedade da terra, tornando-os vulneráveis ao apossamento de fato. À guisa de ilustração, apresentamos dados baseados em um estudo de caso de disputa e atribuição de direitos de propriedade numa importante região agrícola e mineradora localizada ao sul do Pará. Palavras-chave: Política fundiária, direitos de propriedade, instituições de registro de terras This article discusses the Brazilian land problem related to property rights of rural land. After emphasizing the importance of land policies in order to define and distribute rural land properties rights, we show how in Brazil the institutions of rural land registering and cadastering as separated processes debilitates the property rights, making them vulnerable to the effective occupying actions. In order to illustrate it, in this article we analyze Data based in a Case Study of conflict and property rights distributions in an important farming and mining region of southern Para state, in Brazil. Key words: Land policies, right property, registering land institutions.
Keywords: Land policies; Right property; Registering land institutions; Política fundiária; Direitos de propriedade; Instituições de registro de terras